PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT DI LINGKUNGAN MASYARAKAT DESA CORAWALI KECAMATAN BAREBBO KABUPATEN BONE - Sumarni, Sumarni; Susilawati, Susilawati; Emawati, Emawati; Sulfiya Ninsi (Nusantara Hasana Journal, 2023)
The implementation of Clean and Healthy Living Behavior (PHBS) is a vital step in improving public health quality. PHBS includes habits such as washing hands with soap, maintaining environmental cleanliness, consuming nutritious food, and engaging in regular physical activity to prevent infectious and non-communicable diseases. This study aims to evaluate the level of understanding and implementation of PHBS within the community as well as the factors influencing it. The results indicate that public awareness of the importance of PHBS needs to be enhanced through continuous education and the provision of supportive facilities. Collaboration between the government, health institutions, and the community is essential to create a healthy and sustainable environment.